New Azo-Thiadiazole Ligands (Preparation, Spectral, Thermal, Biochemical, Physical properties) - Studying - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
Azo-Thiadiazole  dyes  were  prepared  as  a new  ligands  from  aminothiazole  compound. The  reaction  started  with  coupling  step  of  hydroxyl  benzoic  acid , then  cyclization  step  of  thiosemicabazide  to  produce  thiadiazole  derivative ,  flowed  by  reaction  with   dicarbonyl compounds  to  yield   azo- thiadiazol  ligands. Our new  azo ligands  investigation  by many  chemical  techniques  represented   by  ( I.R,  H.NMR, Mass )- spectra  and  studied   their   behavior  (Thermal , Biochemical  )  with  Physical  properties .  Keywords: Thiazole, Thiadiazol , Cyclization , Esterification , Azo , Sulphobenzoic  acid.